DOI: 10.18174/499098
|View full text |Cite
|
Sign up to set email alerts
|

Protein oxidation as an integrated aspect of plant protein-based food

Abstract: the protein and extracting soluble components (Johnson et al., 2008). The preparation of soy protein isolate (SPI) from the defatted flour involves separation steps under alkaline or acidic conditions (Alibhai et al., 2006;Lawhon et al., 1981).The final step to prepare both SPC and SPI is spray or freeze drying. About 80% of the proteins in SPI are storage globulin proteins: β-conglycinin, formed by three subunits α, α′ and β; and glycinin, composed of acid and basic subunits linked by disulfide bonds (Nishina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 206 publications
(379 reference statements)
0
1
0
Order By: Relevance
“…Deb-Choudhury et al (2020) demonstrated that myofibrillar proteins in animal tissue, like myosin, troponin and collagen are highly prone to oxidative protein modifications. Protein oxidation is correlated to the processing severity of food prepration (Estrada, 2019) and need to be taken into account, while accounting for the potential health effects of Met. Recently, He et al (2022) demonstrated that Met oxidation is responsible for metastasis of pancreatic tumor cells.…”
Section: Role Of Dietary Methionine In Animal Systemsmentioning
confidence: 99%
“…Deb-Choudhury et al (2020) demonstrated that myofibrillar proteins in animal tissue, like myosin, troponin and collagen are highly prone to oxidative protein modifications. Protein oxidation is correlated to the processing severity of food prepration (Estrada, 2019) and need to be taken into account, while accounting for the potential health effects of Met. Recently, He et al (2022) demonstrated that Met oxidation is responsible for metastasis of pancreatic tumor cells.…”
Section: Role Of Dietary Methionine In Animal Systemsmentioning
confidence: 99%